Distance Learning for Food Security and Rural Development: A Perspective from the United Nations Food and Agriculture Organization - McLean, Scott; Gasperini, Lavinia; Rudgard, Stephen (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2002)
This article introduces the work of the United Nations Food and Agriculture Organization (FAO), and describes its interest in the application of distance learning strategies pertinent to the challenges of food security and rural development around the world. The article briefly reviews pertinent examples of distance learning, both from the experience of FAO and elsewhere, and summarises a complex debate about the potential of distance learning in developing countries. The paper elaborates five practical suggestions for applying distance learning strategies to the challenges of food security and rural development. The purpose of publishing this article is both to disseminate our ideas about distance learning to interested professional and scholarly audiences around the world, and to seek feedback from those audiences.